The Effect of Mother Language Toward the Mastery of English Language Acquisition; Case of Indonesian Students in English Learning Process - Hanif Maulaniam Sholah (Tafhim Al-'Ilmi, 2021)
AbstractSecond Language to foreign language acquisition is needed to achieve success in education, workor career and other goals. However, reading a text in a foreign language for non-native speakersrequires language transfer from a foreign language to the mother tongue and then only the meaningand content can be understood. Mother tongue is a language that is absorbed by children up to theage of 3 years. The language transition process requires an appropriate strategy with access tolanguage absorption that is able to facilitate language transfer in the reader's mindset. Analyzingthe strategy and process of language transfer from a foreign language to a mother tongue requiresa measurable and explainable concept or pattern. Analysis of the process of understanding aforeign language is not an easy thing. Due to the difficulty of observing and analyzing the processof understanding a foreign language, the researcher tries to reveal what the role of the mothertongue is in learning and understanding a foreign language. Retrospective interviews with 5Chinese students, 5 Japanese students, 5 Arab students and 5 Indonesian students were carried outby the researcher accompanied by a translator/interpreter by asking some questions about whenforeign language readers use their mother tongue cognitively and how to use their mother tongue ina cognitive way. This cognitive function can help understand the meaning of foreign language texts.The results of this finding contribute to the theory of the process of understanding foreignlanguages from a sociocultural point of view.Keywords: Mother language, Language acquisition, English Learning Process